Tourism, Culture and Heritage in a Smart Economy : Third International Conference IACuDiT, Athens 2016 / Vicky Katsoni; Amitabh Upadhya; Anastasia Stratigea editors - Katsoni, Vickyeditors
Includes bibliographical references pages 499-502